Seropositivity to Campylobacter and association with abortion and lamb mortality in maiden ewes from Western Australia, South Australia and Victoria. Issue 8 (5th June 2022) - Clune, T; Bruce, M; Glanville, E; Campbell, AJD; Lockwood, A; Hancock, S; Thompson, AN; Beetson, S; Brookes, D; Trengove, C; O'Handley, R; Jacobson, C
Abstract : This case‐control study investigated associations between Campylobacter fetus or Campylobacter jejuni titre and reproductive outcomes in 22 flocks of Merino and non‐Merino maiden ewes aged 1–2 years old. Campylobacter titres were also determined for multiparous ewes aged 3 years or older on the same farms. C. fetus 'positivity' (titre ≥1:80) was detected for 12% (57/462; 95% confidence interval [95% CI] 9.6 to 15.6) of maiden ewes and 31% (65/210; 95% CI 25.0 to 37.4) of mature ewes. The odds for failing to rear a lamb in C. fetus ‐'exposed' maiden ewes (titre ≥1:10) was 2.01 times that of seronegative ewes (95% CI 1.09 to 3.77; P = 0.027), but there was no association between C. fetus‐ 'positivity' (titre ≥1:80) and failure to rise (OR 1.69; 95% CI 0.77 to 3.76; P = 0.191). C. fetus abortions were confirmed with microbial culture in one maiden ewe flock. In this flock, C. fetus titres fluctuated and often waned by lamb marking, highlighting the value of necropsies during abortion investigations. C. jejuni‐ 'positivity' (titre ≥1:80) was detected for 44% (204/462; 95% CI 39.7 to 48.7) maiden ewes, but odds of failing to rear were decreased for C. jejuni ‐'positive' ewes (OR 0.52; 95% CI 0.32 to 0.83; P = 0.007). The association between Campylobacter serology and the reproductive outcome was inconsistent in these flocks. Serology should be considered in the context of other risk factors and used in conjunction with other strategies to investigate the impact of Campylobacter exposure on ewe reproductive performance such as monitoring for abortions and lamb necropsies to determine aetiological diagnosis, and vaccination trials.